2018
DOI: 10.1016/s2215-0366(18)30096-8
|View full text |Cite|
|
Sign up to set email alerts
|

Antipsychotic drugs versus cognitive behavioural therapy versus a combination of both in people with psychosis: a randomised controlled pilot and feasibility study

Abstract: SummaryBackgroundLittle evidence is available for head-to-head comparisons of psychosocial interventions and pharmacological interventions in psychosis. We aimed to establish whether a randomised controlled trial of cognitive behavioural therapy (CBT) versus antipsychotic drugs versus a combination of both would be feasible in people with psychosis.MethodsWe did a single-site, single-blind pilot randomised controlled trial in people with psychosis who used services in National Health Service trusts across Grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 33 publications
2
49
0
1
Order By: Relevance
“…As a result, it is not possible to ascertain the respective role of cognitive behavioural therapy and medication on the outcome, neither to evaluate the adequacy of the pharmacotherapy provided in combination with CBT. Moreover, administration of CBT to patients with schizophrenia without concomitant antipsychotic medication is a debated issue: some studies have been conducted by Morrison et al in patients receiving CBT without medication [ 24 , 28 , 29 ], but other authors have claimed this to be unethical [ 30 ]. We argue that the situation in the studies included in the present review resembles real-life clinical practice settings, where patients, in general, receive antipsychotics in addition to CBT, making our results more generalizable to the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is not possible to ascertain the respective role of cognitive behavioural therapy and medication on the outcome, neither to evaluate the adequacy of the pharmacotherapy provided in combination with CBT. Moreover, administration of CBT to patients with schizophrenia without concomitant antipsychotic medication is a debated issue: some studies have been conducted by Morrison et al in patients receiving CBT without medication [ 24 , 28 , 29 ], but other authors have claimed this to be unethical [ 30 ]. We argue that the situation in the studies included in the present review resembles real-life clinical practice settings, where patients, in general, receive antipsychotics in addition to CBT, making our results more generalizable to the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Harms: In Morrison et al (2014) 8 serious adverse events were reported, 2 in the CBT group and 6 in the control group and 2 participants in each group were judged to have a deterioration. In Morrison et al (2018) adverse side-effects (e.g. sleep or memory problems) were less common in the CBT group than the antipsychotics group (p=.017).…”
Section: Cognitive Behavioural Therapy (Cbt)mentioning
confidence: 93%
“…Few studies described how the treatment delivered was standardised and how quality of implementation was assured. The trials of CBT used regular supervision, rated recordings of sessions with a cognitive therapy scale (Blackburn et al, 2001), and reviewed written, structured session records (Morrison et al, 2018(Morrison et al, , 2014. Results are grouped by intervention, including a brief general summary of each intervention.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations